Expresiones socioculturales entorno a la fiesta del Señor de la Buena Esperanza en el Tingo la Esperanza - Cepeda Guzmán, Johanna Estefanía (2018)
The present research project exposes the identification of the different sociocultural expressions around the festival of the Lord of Good Hope in the Parish of Tingo la Esperanza, belonging to the Canton Pujili. In addition, the customs and traditions that characterize this place are described, in the same way a video documentary is presented where the development of the festival in honor of its patron is recorded in order to keep alive the tradition, faith and religiosity that Each year it is renewed with great devotion. In order to determine and identify which are the main reasons why these festivities are carried out, the qualitative method was used; research techniques such as the survey and the interview were also applied. Among the results, which allowed to define that the reasons why these sociocultural expressions are made are the religiosity, faith and devotion that devotees have for their Patron. This project has great relevance due to the need to know the sociocultural expressions and motivations for the celebration of these parties that are held annually, also this place is the meeting point of relatives who live in other cities and in turn admits that others devotees may visit the sanctuary of the Lord of Buena Esperanza. Among the main conclusions it has been determined that the motivators and actors for this celebration to take place are the renewal of the faith and the celebration of the parochialization of this place, since the authorities of the parochial board, together with the ecclesiastical representative are the ones They organize this holiday.